Magmatic evolution of the Boku Volcanic Complex, Main Ethiopian Rift - Tadesse, A; Ayalew, D; Pik, R; Yirgu, G; Fontijn, K (Elsevier, 2018)
The Boku volcanic complex is a Quaternary center situated on the axial segment of the Main Ethiopian Rift (MER), located 92 km South-east from Addis Ababa. The main objective of this study is to understand the magmatic evolution of the volcanic complex and to develop a model to answer some outstanding questions related to bimodal products of rift related volcanism, using geological mapping, petrographic and geochemical approaches. The Boku complex is characterized by two main phases of activity: pre-caldera/caldera forming eruptive activity and post-caldera eruptive activity. The volcanic stratigraphy consists from bottom to top of a sequence of rhyolitic lava flows, pumice flows, welded ignimbrite, pumice fall, rhyolitic lava dome, obsidian flow, lower basaltic lava flow, ash flow, basaltic scoria and upper basaltic lava flows. The lithologic varieties together with the geochemical results indicate that the Boku eruptive products are bimodal in composition; no intermediate compositions are found. The mafic rocks are transitional to weakly subalkaline basalts while the silicic rocks are predominantly peralkaline rhyolites. These two groups of rocks are co-genetic and related to each other by fractional crystallization processes starting from mantle-derived basaltic magma with a small component of crustal contamination. The available geophysical, geochemical and field data suggest that the evolution of the evolved silicic center which hosts a bimodal rock distribution can be explained as a result of prolonged stagnation of transitional basaltic melt (sourced from the mantle) at relatively high pressures, where these evolve to intermediate compositions. The transitional basaltic melts can occasionally erupt to the surface along weakness lines such as faults that infrequently cut the lower part of the shallow reservoir, generating basalts from the intra-caldera and lateral eruptive centers. We consider the intermediate magma is mechanically trapped at mid-crustal depths because of its higher crystal load (ca. 50%). Silicic magma is formed at shallow depth by prolonged fractional crystallization of the intermediate magma and minor assimilation of crustal material. These silicic magmas generate both effusive and explosive eruption products in the overall stratigraphy of the volcanic complex.